2009
DOI: 10.1016/j.jcrs.2008.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Corneal collagen crosslinking using riboflavin and ultraviolet-A light for keratoconus

Abstract: Stable BCVA, spherical equivalent, anterior and posterior corneal curvatures, and corneal elevation 1 year after crosslinking indicate that keratoconus did not progress. Unchanged lens density and foveal thickness suggest that the lens and macula were not affected after UVA exposure during crosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
115
5
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 33 publications
21
115
5
5
Order By: Relevance
“…Our findings show that the lower resistance to deformation in keratoconus group is not due only to thinning, because the groups were matched by thickness. Additionally, higher corneal resistance after collagen cross-linking is often accompanied by thinning (28)(29) . Therefore, corneal rigidity and resistance to deformation are likely affected by unknown factors in addition to corneal thickness (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the lower resistance to deformation in keratoconus group is not due only to thinning, because the groups were matched by thickness. Additionally, higher corneal resistance after collagen cross-linking is often accompanied by thinning (28)(29) . Therefore, corneal rigidity and resistance to deformation are likely affected by unknown factors in addition to corneal thickness (12) .…”
Section: Discussionmentioning
confidence: 99%
“…5,6,15 Numerous clinical studies agreed that CXL treatment provides significant improvements in visual acuity and maximum keratometry as well as halting the progression of keratoconus. 7,8,16,17 However, it is still unclear whether baseline demographic and topographic characteristics influence postoperative outcomes. Therefore, we sought effects of age, gender, preoperative CDVA, preoperative maximum K, topographic cone location, and preoperative thinnest corneal pachymetry on improvements in CDVA and maximum K at 1 year after CXL treatment.…”
Section: Eyementioning
confidence: 99%
“…Specifically, K max became flatter by 0.58 ± 1.37 D (p = 0.02), which is similar to multiple other studies. 12,14,16,17,[21][22][23][24][25][26][27] The trend is for significant flattening of the central steeper curvature. Of interest, the peripheral keratometry measurements found the inferior and temporal cornea to become flatter, with superior and nasal cornea becoming steeper.…”
Section: Discussionmentioning
confidence: 97%
“…By comparison, Grewal et al found no change in central posterior curvature at one year. 21 Vinciguerra et al assessed the posterior surface using elevation maps and found no significant difference at one year. The central corneal pachymetry measurements were significantly thinner at 6 months, with a rebound to be similar readings at the one year mark compared to preoperative levels.…”
Section: Discussionmentioning
confidence: 99%